2010
DOI: 10.3109/0284186x.2010.509104
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I study of recombinant human interleukin-21 (rIL-21) in combination with sunitinib in patients with metastatic renal cell carcinoma (RCC)

Abstract: (2011) A Phase I study of recombinant human interleukin-21 (rIL-21) in combination with sunitinib in patients with metastatic renal cell carcinoma (RCC), Acta Oncologica, 50:1, 121-126,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…It also regulates the proliferation, survival, differentiation and effector functions of NK cells (1,5,16). As a promising cytokine for cancer immunotherapy, IL-21 has been undergoing Phase I and II testing in clinical trials for the treatment of early phase renal cell carcinoma and melanoma (17)(18)(19).…”
Section: T Cells and Nk T Cells (1-4) Its Receptor (Il-21r)mentioning
confidence: 99%
See 1 more Smart Citation
“…It also regulates the proliferation, survival, differentiation and effector functions of NK cells (1,5,16). As a promising cytokine for cancer immunotherapy, IL-21 has been undergoing Phase I and II testing in clinical trials for the treatment of early phase renal cell carcinoma and melanoma (17)(18)(19).…”
Section: T Cells and Nk T Cells (1-4) Its Receptor (Il-21r)mentioning
confidence: 99%
“…It also regulates the proliferation, survival, differentiation and effector functions of NK cells (1,5,16). As a promising cytokine for cancer immunotherapy, IL-21 has been undergoing Phase I and II testing in clinical trials for the treatment of early phase renal cell carcinoma and melanoma (17)(18)(19).Accumulated data have shown that tumors may exploit certain inhibitory checkpoints and pathways to escape immune attack, even in the face of a strongly induced antitumor immune response. In these tumor-escaping mechanisms, the expression of programmed death ligand 1 (PD-L1) by the tumor may play an important role in its resistance to immune destruction (20).…”
mentioning
confidence: 99%
“…Additionally, IL-21 and IL-21R were increased in all transplanted organs to a similar extent and might promote graft-versus-host disease (GVHD) by enhancing the production of effector CD4 + T cells [102,103]. Recent studies revealed the potent pleiotropic effects of IL-21 in pulmonary disorders [104,105], renal diseases [106,107] and diabetes [108,109] …”
Section: Discussionmentioning
confidence: 99%
“…82). It is also noteworthy that dose-limiting toxicities have been observed in patients with RCC treated with the targeted agent sunitinib and either rhIL21 (hematologic toxicity) or the anti-CTLA-4 agent tremelimumab (renal failure), further emphasizing the need for caution when evaluating combinations (83,84).…”
Section: Clinical Experience and Considerations In Combining Novel Immentioning
confidence: 99%